INTEGRATING TECHNOLOGY INTO LANGUAGE TEACHING: BEST PRACTICES AND EMERGING TRENDS - Indrastana, Nodistya Septian (TRANSFORMATIONAL LANGUAGE, LITERATURE, AND TECHNOLOGY OVERVIEW IN LEARNING, 2022)
The rapid advancements in technology have transformed the landscape of language teaching, presenting new opportunities and challenges for educators. As educators seek to enhance the effectiveness of language instruction, the integration of technologies such as digital resources and online platforms has become essential in fostering student engagement and promoting language competence. The purpose of this study was to examine the integration of technology into language teaching by exploring the literature on the use of technology in English as a Foreign Language learning. Drawing on a comprehensive literature review, the researchers adopted a descriptive qualitative approach to gain insights into how EFL students perceive and engage with the use of technology in their language learning. This investigation aimed to uncover the benefits, challenges, and emerging trends associated with incorporating digital tools and resources into EFL curricula, ultimately informing best practices for the effective integration of technology to support and enhance language acquisition. The adoption of innovative digital tools not only caters to diverse learning styles but also enhances interaction and understanding among students, ultimately leading to a more immersive learning experience in the language classroom.